Twisted - Hovey, Kate (University of Virginia, 2026)
A project created for both DRAM 2620 - Sound Design and ARTS 200 - Intro to Studio Art. A mixed-media stop motion animation with original sound design.
Original submission date: 2026-03-23T18:48:37Z
Keywords: Animation; Stop Motion; Class Project; Sound Design; Claymation